2014
DOI: 10.1002/etc.2810
|View full text |Cite
|
Sign up to set email alerts
|

Cross-basin comparison of mercury bioaccumulation in Lake Huron lake trout emphasizes ecological characteristics

Abstract: Understanding factors influencing mercury (Hg) bioaccumulation in fish is important for examining both ecosystem and human health. However, little is known about how differing ecosystem and biological characteristics can drive Hg bioaccumulation in top predators. The present study compared and contrasted Hg bioaccumulation in multiple age classes of lake trout (Salvelinus namaycush) collected from each of Lake Huron's Georgian Bay, North Channel, and Main Basin regions. Mercury concentrations exhibited a basin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
5
6
0
Order By: Relevance
“…Abma et al [36] recently demonstrated basin-specific mercury biomagnification patterns for Lake Huron lake trout that mirror those observed for PCBs in the present study. This pattern was independent of any trophic-level effects or significant increase in Georgian Bay prey fish mercury concentrations relative to Main Basin and North Channel prey [36]. Trudel and Rasmussen [37] proposed that such Hg bioaccumulation dynamics in lake trout will be highly dependent on prey acquisition and energy assimilation strategies.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Abma et al [36] recently demonstrated basin-specific mercury biomagnification patterns for Lake Huron lake trout that mirror those observed for PCBs in the present study. This pattern was independent of any trophic-level effects or significant increase in Georgian Bay prey fish mercury concentrations relative to Main Basin and North Channel prey [36]. Trudel and Rasmussen [37] proposed that such Hg bioaccumulation dynamics in lake trout will be highly dependent on prey acquisition and energy assimilation strategies.…”
Section: Discussionsupporting
confidence: 89%
“…Such prey search activities are among the primary regulators of fish growth as a result of the increased frequency of search activity required in reduced prey environments . Abma et al recently demonstrated basin‐specific mercury biomagnification patterns for Lake Huron lake trout that mirror those observed for PCBs in the present study. This pattern was independent of any trophic‐level effects or significant increase in Georgian Bay prey fish mercury concentrations relative to Main Basin and North Channel prey .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The PCB bioaccumulation patterns we have demonstrated in Lake Huron fish also demonstrate the utility of lake trout as a biomonitor in that basin-specific congener profiles evident in this top predator are conserved among lower trophic level species for which bottom-up processes regulate pollutant exposure. Furthermore, our results and those of Abma et al (2015), Paterson et al (2016), andMcLeod et al (2019) support continued monitoring programs that emphasize the importance of basin-specific management strategies for quantifying and understanding the roles of multiple stressors on pollutant bioaccumulation and biomagnification in Great Lakes ecosystems. Specifically, although the transfer of energy and pollutants in Lake Huron's Main Basin, Georgian Bay, and North Channel food webs are facilitated by predator-prey interactions among the same species and similar hierarchical trophic structures, it is potentially differences in the strengths of such interactions within lower trophic levels that regulate energy flow and PCB bioaccumulation patterns in these food webs (Bartley et al 2019).…”
Section: Discussionsupporting
confidence: 69%
“…However, the extent to which such ecological restructuring has occurred in the food webs from each of Lake Huron's 3 basins remains unknown. Recent studies have demonstrated contrasting responses among Lake Huron lake trout with respect to mercury (Hg) and polychlorinated biphenyl (PCB) bioaccumulation in fish collected from each of the lake's 3 basins (Abma et al 2015;Paterson et al 2016). These include a general concentration gradient for Hg and total PCB concentrations with Main Basin > Georgian Bay > North Channel fish and unique PCB congener profiles for fish depending on the basin of collection (Abma et al 2015;Paterson et al 2016).…”
Section: Introductionmentioning
confidence: 99%